Eleanor Spear papers - Spear, Eleanor, 1910-2006.
Correspondence, typescript titled "Radio Talk," newspaper clippings, and other papers chiefly concerning Spear's activities as a pioneer in women's aviation while a student at Wellesley College. Includes correspondence, constitution, bylaws, and ballot relating to Ninety-Nines, an organization established in 1929 by 99 women air pilots to provide support for women in aviation. Correspondents include Amelia Earhart and Teva Paris.
Aviator.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Earhart, Amelia, -- 1897-1937 -- Correspondence; Paris, Teva -- Correspondence; Ninety-Nines (Organization); Wellesley College -- Students; Aeronautics; Aeronautics -- Societies, etc; Women air pilots; Air pilots; Women in aeronautics; Aviators